Precision Injection of Dairy Sludge on Crop Yield and N and P Uptake in Juvenile and Mature No-Till Silage Corn - Derek E. Hunt; Shabtai Bittman (Agronomy, 2021)
Starter mineral fertilizer is used by famers to provide phosphorus (P) and nitrogen (N) to emerging corn (Zea mays) plants. Recent studies have shown that dairy slurry can replace mineral fertilizer provided it is precisely positioned close to the corn rows. This 5-year study examined the multi-year effect of precision injected sludge, the thick fraction separated from dairy slurry, on growth and nutrient uptake at the 6-leaf stage and final harvest of no-till corn. The sludge was first injected 15 cm deep and the corn planted < 10 cm from the sludge furrow at least 3 days later. Sludge provided sufficient P for both early growth and full season growth. At final harvest with equivalent total N and P rates (32P 250N treatments), fertilizer and sludge had similar maximum yields (17.9 and 17.4 t ha−1, respectively) and P uptake (26 and 25 kg ha−1, respectively) but fertilizer had higher N uptake than sludge (200 and 162 kg ha−1). N uptake and recovery N use efficiency was greater for sludge than fertilizer based on equivalent min.-N which suggests crop benefits in the sludge other than min-N and P. The study shows that precisely injected dairy sludge can obviate the need for starter mineral fertilizer, and this may help to alleviate P surpluses on dairy farms. This practice also provides a use on dairy farms for the separated solids fraction remaining after the thin fraction is decanted and applied as the primary N source to grass.